The Psychological Factors Inciting Religiously motivated Violent Radicalism - Shirinov, Agil (Scholarya Demo Journal of Ruby, 2019)
Hundreds of researches are devoted to the role of psychological factors inciting violent radicalism dispositions in people’s mind. These researchesdiscuss the issue questioning whether tendency to violence is inherent in humannature or not, the possibility of common psychological traits of the personsinclined to radicalism and the impact of social environment and ideologies onpersonality. The article discusses the theories studying whether tendency to violence isinherent in human nature or not and concludes that the factors inciting humansto violence derive from various sources. Childhood experiences, interpersonal social relations and radical world outlook are mentioned along with the factorsthat are inherent to human nature. The second part of the article discusses religiously motivated violent radicalism in psychological setting and concludes that the process of involvement in radical groups has a multifaceted character. Furthermore, it emphasizes that reductionist theories fail to fully solve the problem by explaining the factors from the aspect of individual psychological characteristics. According to the author, it is impossible to mention a personality type with radical identity from the psychological aspect. Although the article highlights that the individuals with unstable psychological character are more vulnerable to radicalism, it suggests the necessity of studying radicalization and involvement in radical groups from the psychological as well as the socio-political and ideological aspects.